PERBEDAAN PROFESIONALISME AUDITOR DITINJAU DARI PERPSPEKTIF GENDER - Utami, Ratna (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
This Research aim to to know auditor professionalisme in running its work with case study laboring auditor at KAP in Malang. Result of research indicate that man auditors and woman auditors have professionally in running its work. While in different test with test of t indicate that there no difference of professionalisme between men auditor and woman auditor in running work. This matter is proved by doing/conducting examination to five dimension to measure professionalism that is dedication to professionalism, professionalism standard, autonomy, socia obligation and community affiliation. Public accounting profession as an independent third party plays an important role to judge the fairness of the financial statements presented accountability by management.